Academic Supervision Of The State Principal School (Evaluative Study in Rejang Lebong Regency, Indonesia) - Haimah Haimah; Bambang Sahono; Manap Somantri; Connie Connie (Institut Agama Islam Negeri (IAIN) Curup, 2021)
This study aims to evaluate the academic supervision program of the principal of a public elementary school in Rejang Lebong Regency, Indonesia. This research is an evaluation study of the CIPP model with a qualitative approach. The subjects of this study were principals and teachers of public elementary schools in Rejang Lebong Regency. Techniques for data collection include observation, interviews, and documentation, as well as data reduction, data presentation, and verification. The outcomes of the study reveal that, first, the setting of the principal's academic supervision program does not meet the criteria. There are still numerous flaws, such as the principal's lack of understanding of the notion of academic supervision, which has prevented them from properly developing program planning. Second, the input of the academic supervision program has not fully supported the program, there are still many shortcomings such as no stakeholder support, and not being able to find the right strategy both in planning and in program implementation. Third, the process of the academic supervision program has not been following the plan, such as the program implementation steps. Fourth, the product of the academic supervision program has not shown an increase in teacher performance. However, both teachers and principals want the principal's academic supervision program to continue by correcting all its shortcomings and weaknesses. The conclusion of the academic supervision program of the principal of the public elementary school in Rejang Lebong Regency as a whole has not been fulfilled but is continuing with improvements, both in terms of context, input, process, and product aspects. For this reason, in this study, the author offers a model of academic supervision training based on KKS and KKG through mentoring.